Mixed plastics waste valorization to high-added value products via thermally induced phase separation and spin-casting - Saleem, Junaid (2024)
Plastic waste is an underutilized resource that has the potential to be transformed into value-added materials. However, its chemical diversity leads to cost-intensive sorting techniques, limiting recycling and upcycling opportunities. Herein, we report an open-loop recycling method to produce graded feedstock from mixed polyolefins waste, which makes up 60% of total plastic waste. The method uses heat flow scanning to quantify the composition of plastic waste and resolves its compatibility through controlled dissolution. The resulting feedstock is then used to synthesize blended pellets, porous sorbents, and superhydrophobic coatings via thermally induced phase separation and spin-casting. The hybrid approach broadens the opportunities for reusing plastic waste, which is a step towards creating a more circular economy and better waste management practices.